Monitoring the John Cunningham virus throughout natalizumab treatment in multiple sclerosis patients. (25th October 2015) - Domínguez‐Mozo, M. I.; García‐Montojo, M.; Arias‐Leal, A.; García‐Martínez, Á.; Santiago, J. L.; Casanova, I.; Galán, V.; Arroyo, R.; Fernández‐Arquero, M.; Alvarez‐Lafuente, R.
Abstract : Background and purpose: Progressive multifocal leukoencephalopathy (PML) cases have arisen amongst multiple sclerosis patients treated with natalizumab. Our objective was to gain a better understanding of the mechanisms that underlie the John Cunningham virus (JCV) infection which causes PML. Methods: A study was made of (i) the quarterly JCV DNA levels in peripheral blood mononuclear cells (PBMCs), serum and urine samples in 100 multiple sclerosis patients during their natalizumab treatment (3–39 months), (ii) the association between human leukocyte antigen (HLA) class II and the previous viral detection and (iii) the identification of the JCV variants in those patients suspected of having PML. Results: (i) JCV DNA in PBMCs and/or serum was detected in 23% of our cohort. Patients with an intermittent JCV excretion in urine had a significant increase of the viral load and prevalence in this compartment during natalizumab treatment. (ii) The frequency of the DRB1*07/DQA1*02:01/DQB1*02:02 haplotype tended to be higher in patients with detectable versus undetectable JCV DNA in PBMCs ( P corrected = 0.108). (iii) The variants in PBMCs and serum of the non‐PML patient matched the archetype. In the patient with non‐fatal PML, the archetype and the same neurotropic variant in PBMCs, serum and cerebrospinal fluid was identified at the time PML was diagnosed, whereas in the patient with a worse PML prognosis, four neurotropic variants in the three previous compartments were found by the PML diagnosis. Conclusions: The detection of the neurotropic variant in blood during natalizumab treatment could be critical in the prevention of the development of severe PML, since this variant appears simultaneously with the clinical symptoms of PML and mutates quickly.